ASSET GROWTH, LEVERAGE DAN RETURN ON EQUITY SEBAGAI FAKTOR DIVIDEND PAYOUT RATIO PADA PERUSAHAAN INDEKS LQ45 TAHUN 2014-2018 - Suci Mahfiroh; Ermalina Ermalina (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2021)
The purpose was to analyzed Asset Growth, Leverage and ROE as factor that has impact on Dividend Payout Ratio on LQ45. Used quantitative and purposive sampling method with an associative approach that listed on the Indonesia Stock Exchange in 2014-2018. The results showed that Asset growth and leverage have a significant and insignificant negative effect, but ROE has a positive and insignificant effect on the Dividend Payout Ratio, which mean company must be able to manage growth assets properly and be able to pay each of its obligations by utilizing the profits earned because it can affected the size of its small company in distributing dividends. This showed that a company must be able to manage asset growth properly.